SDR-2 as a strong candidate vaccine for brucellosis in animals - Maxs U.E Sanam (Indonesian Center for Animal Research and Development (ICARD), 2001)
Various mutant strains of Brucella suis type-1 have been recently developed including SDR-2 and SD-7. This research was aimed at revealing the course of infection and serological reactions, as well as the protection capacity of these mutant strainscompared to the reference vaccine strain 19, and the virulent strain B. suis type-1 in Quackenbush mice as a model. Antibody reactions were measured by an Enzyme-linked Immunosorbent Assay (ELISA) and degree of infection was determined by bacterial spleen count. The results showed that the SD-7 was unable to perform infection in mice. Whereas SDR-2, strain 19 and the virulent B. suis type-1 were able to colonize the mice spleens with varying rate of infections. The inoculation of SDR-2 to the mice produced mild infection and lasted shorter than the virulent strain even with the reference vaccine strain 19. The number of SDR-2 and strain 19 organisms were sharply dropped at week-12 post inoculation while that of virulent strain was significantly remained high. Serological responses induced by SDR-2 was the lowest followed by those of strain 19, and the virulent strain. On the challenge with a virulent B. suis, histological examinations of the spleen of the control mice revealed that there was a marked depletion of lymphoid cells and reticuloendothelial hyperplasia in lymphoid follicles. However no significant pathological changes were observed in groups inoculated with either SDR-2 or Strain 19. Enumeration of survival challenge organisms in the spleens clearly demonstrated that SDR-2 provided significant protection (2.17 Log10) to the animals which was comparable to that provided by strain-19 (2.20 Log10). In conclusion, SDR-2 has a potential as a vaccine for use in pigs against Brucella suis infection. Furthermore SDR-2 offers some advantages over strain 19 in that it is less virulent and induces less antibody responses than the strain 19 and thus may have application in other animals. However, furher study on its efficacy as a vaccine for brucellosis in pigs as the primary host for B. suis needs to be assessed. Key words: Brucella suis, mutant strains, SDR-2 vaccine, strain 19, antibody